2000
DOI: 10.1017/s0021963099005946
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Functional Impairment in Children and Adolescents

Abstract: The goal of this study was to investigate the variables that best predict functional impairment in children and adolescents. Two hundred and eight psychiatric and 129 pediatric children aged 7 to 17 years were assessed with measures of psychopathology, functional impairment, temperament, marital discord, educational style, coping, developmental milestones, stressful life events, medical history, school information, and family history of psychopathology. Multiple regression models adjusted by psychopathology we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…As children get older, psychological symptoms are more distressful. Studies about impairment have previously reported that psychological disorders are more severe in adolescents than in children (Ezpeleta, Granero, de la Osa, & Guillamon, 2000). Furthermore, it seems from our results that adolescents suffer from more severe disorders that cause them more discomfort relative to children, or else they are better able to identify this feeling.…”
Section: Discussionsupporting
confidence: 45%
“…As children get older, psychological symptoms are more distressful. Studies about impairment have previously reported that psychological disorders are more severe in adolescents than in children (Ezpeleta, Granero, de la Osa, & Guillamon, 2000). Furthermore, it seems from our results that adolescents suffer from more severe disorders that cause them more discomfort relative to children, or else they are better able to identify this feeling.…”
Section: Discussionsupporting
confidence: 45%
“…It comprises 54 items to assess nine dimensions including: general activity level; sleep activity; approach/withdrawal; flexibility/rigidity; mood; sleep rhythmicity; eating rhythmicity; daily rhythmicity; and task orientation (Windle & Lerner, 1986 The DOTS-R has demonstrated sound psychometric characteristics across age groups, including pre-school children (Windle & Lerner, 1986). Although not tested for reliability and validity in Australia, testing in several countries provides evidence of cross-cultural validity (Ezpeleta, Granero, de la Õ sa, & Guillamon, 2000;Koot, 1991;Mednick, Hocevar, Schulsinger, & Baker, 1996).…”
Section: Sleep Rhythmicitymentioning
confidence: 99%
“…Functional impairment and mental health problems thus conceptually are closely linked, and empirically a range of child mental health problems have been found to serve as risk factors for functional impairment [79]. In fact, functional impairment often has been found to be a stronger predictor of service utilization than the mental health symptoms themselves, and ultimately it is an independent construct [10]. This is true in part because other factors (e.g., medical problems) have been found to predict child functional impairment independent of mental health problems, significant functional impairment occurs among children with relatively low levels of mental health symptoms [11,12], and functional impairment predicts other service usage (e.g., special education) in addition to health service usage, independently of mental health problems [6].…”
Section: Introductionmentioning
confidence: 99%